"Bio-glues" to enhance slipperiness of mucins: improved lubricity and wear resistance of porcine gastric mucin (PGM) layers assisted by mucoadhesion with chitosan. Issue 3 (21st November 2014) - Nikogeorgos, Nikolaos; Efler, Petr; Kayitmazer, A. Basak; Lee, Seunghwan
Abstract : A synergetic lubricating effect between porcine gastric mucin (PGM) and chitosan based on their mucoadhesive interaction is reported at a hydrophobic interface comprised of self-mated polydimethylsiloxane (PDMS) surfaces. Abstract : A synergetic lubricating effect between porcine gastric mucin (PGM) and chitosan based on their mucoadhesive interaction is reported at a hydrophobic interface comprised of self-mated polydimethylsiloxane (PDMS) surfaces. In acidic solution (pH 3.2) and low concentrations (0.1 mg mL −1 ), the interaction of PGM with chitosan led to surface recharge and size shrinkage of their aggregates. This resulted in higher mass adsorption on the PDMS surface with an increasing weight ratio of [chitosan]/[PGM + chitosan] up to 0.50. While neither PGM nor chitosan exhibited slippery characteristics, the coefficient of friction being close to 1, their mixture improved considerably the lubricating efficiency (the coefficient of friction is 0.011 at an optimum mixing ratio) and wear resistance of the adsorbed layers. These findings are explained by the role of chitosan as a physical crosslinker within the adsorbed PGM layers, resulting in higher cohesion and lower interlayer chain interpenetration and bridging.